Analysing the Foreign Policy of Small States in the EU - Larsen, H. author. aut Link
XIV, 242 p.
Keywords: Can a distinct national foreign policy still be identified for small EU member states, and what accounts for the balance between national and EU foreign policy? Henrik Larsen develops an analytical framework for analyzing these questions and offers solutions through an empirical examination of the foreign policy of a small EU member state in the context of EU foreign policy - the case of Denmark. The book looks at seven policy areas: policy towards other EU member states, anti-terrorism, development, the Balkans, Africa, Latin America and trade. On the basis of the empirical study, the implications for the theoretical study of national foreign policy in an EU Context are outlined. It is suggested that we need a new, mixed approach to foreign policy analysis within the EU taking into account the nature of the policy area concerned and national conceptions of actorness.